2018
DOI: 10.1149/2.0181808jes
|View full text |Cite
|
Sign up to set email alerts
|

Review—Power Sources for the Internet of Things

Abstract: Wireless sensor networks have become integral to enabling numerous applications for the Internet of Things, such as environmental sensing or healthcare monitoring. Powering these networks has been the focus of significant research efforts due to the need for reliable and continuous operation of the sensing nodes. In this review, we outline the progress made in the sensing nodes with a particular focus on their power demands. These requirements are used as a framework for surveying the theoretical limits and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 64 publications
(98 reference statements)
0
104
0
Order By: Relevance
“…The power consumption of a low-powered IoT device typically ranges between 20 mW and 10 mW, 31,54 and SiNC-HPVs enables sufficient power supply to the IoT device by designing an optimum system structure. A typical fullerene-based OPV has been reported to exceed a PCE of 10% under a simulated indoor light source.…”
Section: Device Performance Under Standard Indoor Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…The power consumption of a low-powered IoT device typically ranges between 20 mW and 10 mW, 31,54 and SiNC-HPVs enables sufficient power supply to the IoT device by designing an optimum system structure. A typical fullerene-based OPV has been reported to exceed a PCE of 10% under a simulated indoor light source.…”
Section: Device Performance Under Standard Indoor Lightmentioning
confidence: 99%
“…[28][29][30] In recent years, due to the rapid development of IoT (Internet of Things) related technology, the number of IoT devices has dramatically increased. 31,32 Many type of printable PV devices such as OPVs, [33][34][35][36][37][38][39][40][41][42] dye-sensitized solar cells 43,44 and perovskite solar cells 45,46 have been explored for indoor applications, OPVs are especially expected to be used as an energy harvesting system for IoT devices because of their potential for low power operation, independent and distributed applications, high portability and device designability. In this study, we successfully demonstrated SiNC-HPVs with PCE as high as 9.7% and power density of 34.0 mW cm À2 under standard indoor light irradiation (1000 lx).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, current IoT design goals require modern approaches that can achieve minimal power consumption and minimal processing times [2]. This research direction is very important, especially in batterypowered or harvesting IoT platforms [3].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the rapid expansion of the Internet of Things (IoTs) technology, power supply for IoT devices has become one of the major concerns limiting their expansion [1]. a-Si:H thin film solar cells have attracted considerable attention as power supplies for IoT devices because of their thin, flexible, and light-weight features, as well as their low production cost compared to other solar cells [1].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the rapid expansion of the Internet of Things (IoTs) technology, power supply for IoT devices has become one of the major concerns limiting their expansion [1]. a-Si:H thin film solar cells have attracted considerable attention as power supplies for IoT devices because of their thin, flexible, and light-weight features, as well as their low production cost compared to other solar cells [1]. However, to ensure a-Si:H thin film solar cells remain highly efficient, it is necessary to suppress light-induced degradation [2][3][4][5][6][7][8][9][10] by lowering the density of the Si-H 2 bonds in a-Si:H films [6].…”
Section: Introductionmentioning
confidence: 99%